تأثير استخدام تمرينات ثبات المركز لتنمية بعض مؤشرات الحالة البدنية والفسيولوجية وتحسين بعض المهارات الأساسية على جهاز المتوازيين لطلاب كلية التربية الرياضية - مسعود، صالح مسعود فرج عثمان; الجمال، أحمد سمير علي منصور (جامعة الأسكندرية - كلية التربية الرياضية للبنات, 2023)
يهدف البحث إلى التعرف على تأثير استخدام تمرينات ثبات المركز لتنمية بعض مؤشرات الحالة البدنية والفسيولوجية وتحسين بعض المهارات الأساسية على جهاز المتوازيين لطلاب كلية التربية الرياضية بنها وطبقت هذه الدراسة على (50) طالب من كلية التربية الرياضية بواقع 100% من أجمالي مجتمع البحث عام (2022م) لمدة (12) أسبوع بواقع ثلاث وحدات تدريبية في الأسبوع. وكانت أهم النتائج أن تمرينات ثبات المركز عملت على تنمية بعض مؤشرات الحالة البدنية والفسيولوجية وتحسين بعض المهارات الأساسية على جهاز المتوازيين لطلاب كلية التربية الرياضية حيث أن تأثير استخدام تمرينات ثبات المركز لها تأثير إيجابيا كبير جدا على تحسن المجموعة التجريبية بالمقارنة بالمجموعة الضابطة الأقل في النسبة المئوية وكانت اهم التوصيات ضرورة الاهتمام بتمرينات ثبات المركز لتأثيرها الإيجابي على تنمية وتحسين الحالة البدنية وكذلك المهارية على أجهزة الجمباز الأخرى التي لم تمارس عليها هذه التمرينات لطلاب كلية التربية الرياضية. The research aims to identify the effect of using center stability exercises to develop some indicators of physical and physiological condition and improve some basic skills on the parallel system for students of the Faculty of Physical Education in Benha. This study was applied to (50) students from the Faculty of Physical Education at a rate of %100 of the total research community in 2022 AD. ) for a period of (12) weeks, with three training units per week The most important results were that the stability exercises of the center worked to develop some indicators of physical and physiological condition and improve some basic skills on the parallel apparatus for students of the Faculty of Physical Education, as the effect of using center stabilization exercises had a very large positive effect on the improvement of the experimental group compared to the control group in the lowest percentage. The most important recommendations are the need to pay attention to the stability exercises of the center for their positive impact on the development and improvement of the physical condition, as well as the skill on other gymnastics equipment that these exercises were not practiced for students of the Faculty of Physical Education.
Keywords: طلبة الجامعات -- التمرينات الرياضية -- اللياقة البدنية